Respiratory syncytial virus infection and disease in infants and young children observed from birth in Kilifi District, Kenya. - Nokes, D; Okiro, E; Ngama, M; Ochola, R; White, L; Scott, P; English, M; Cane, P; Medley, G (2008)
BACKGROUND: In developing countries, there are few data that characterize the disease burden attributable to respiratory syncytial virus (RSV) and clearly define which age group to target for vaccine intervention. METHODS: Six hundred thirty-five children, recruited during the period 2002-2003, were intensively monitored until each experienced 3 epidemics of RSV infection. RSV infection was diagnosed using immunofluorescence of nasal washing specimens collected at each episode of acute respiratory infection. Incidence estimates were adjusted for seasonality of RSV exposure. RESULTS: For 1187 child-years of observation (CYO), a total of 409 (365 primary and 82 repeat) episodes of RSV infection were identified. Adjusted incidence estimates of lower respiratory tract infection (LRTI), severe LRTI, and hospital admission were 90 cases per 1000 CYO, 43 cases per 1000 CYO, and 10 cases per 1000 CYO, respectively, and corresponding estimates among infants were 104 cases per 1000 CYO, 66 cases per 1000 CYO, and 13 cases per 1000 CYO, respectively. The proportion of cases of all-cause LRTI, and severe LRTI and hospitalizations attributable to RSV in the cohort was 13%, 19%, and 5%, respectively. Fifty-five percent to 65% of RSV-associated LRTI and severe LRTI occurred in children aged >6 months. The risk of RSV disease following primary symptomatic infection remained significant beyond the first year of life, and one-quarter of all reinfections were associated with LRTI. CONCLUSIONS: RSV accounts for a substantial proportion of the total respiratory disease in this rural population; we estimate that 85,000 cases of severe LRTI per year occur in infants in Kenya. The majority of this morbidity occurs during late infancy and early childhood--ages at which the risk of disease following infection remains significant. Disease resulting from reinfection is common. Our results inform the debate on the target age group and effectiveness of a vaccine.